2019
DOI: 10.1021/acssuschemeng.9b06267
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Carbon Dots toward Anti-Counterfeiting

Abstract: The synthesis of carbon dots (CDs) from green precursors has received considerable attention recently. However, most of the natural biomass-derived products without further surface treatment usually have quite low quantum yield (QY) varying in the range of 2–30%. Herein, we report the sustainable fabrication of highly fluorescent CDs from food waste, turtle shells, and demonstrate their applications in the fields of multisignal coding and anti-counterfeiting with a combination of colloidal photonic crystals (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 47 publications
1
92
0
Order By: Relevance
“…56,76,[93][94][95] Many precursors from biomass have been used to produce C-dots via pyrolysis reactions. 56,76,[93][94][95] For instance, Martindale's group reported the synthesis of C-dots by pyrolyzing CA at 180 1C with a yield of 45% and a size of 6.8 AE 2.3 nm. 93 Wang et al reported the large-scale and controllable synthesis of C-dots with a yield of 15% from rice husk.…”
Section: Pyrolysis Carbonization Synthesis Of C-dotsmentioning
confidence: 99%
“…56,76,[93][94][95] Many precursors from biomass have been used to produce C-dots via pyrolysis reactions. 56,76,[93][94][95] For instance, Martindale's group reported the synthesis of C-dots by pyrolyzing CA at 180 1C with a yield of 45% and a size of 6.8 AE 2.3 nm. 93 Wang et al reported the large-scale and controllable synthesis of C-dots with a yield of 15% from rice husk.…”
Section: Pyrolysis Carbonization Synthesis Of C-dotsmentioning
confidence: 99%
“…The bandgap derived from highly ordered periodic structures is responsible for uniformly reflected colours in the visible spectrum. Accordingly, a variety of techniques, like photolithography [ 4 ], screen printing [ 5 ], atomisation deposition [ 6 ], inkjet printing [ 7 , 8 ], spray coating [ 9 , 10 ], gravity sedimentation [ 11 , 12 ], and electrophoretic deposition [ 13 , 14 ], have been proposed for the adhibition by applying photonic crystals onto substrates in several applications, including paints and inks [ 5 ], smart windows [ 3 ], energy-saving devices [ 15 ], night-time traffic safety and advertisement display [ 16 ], anti-counterfeiting security [ 4 , 17 , 18 ], eyeglasses and photographic lenses [ 19 ], and information storage [ 20 ]. To realise such promising industrial applications, the studies on the large-area scalable fabrication technique of photonic crystals have been conducted, including melt-shear organization method [ 21 ] and oscillatory shear technique [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we propose the use of a novel material for traffic warning displays in both sunny and rainy days. The previously published literatures have provided evidence that Poly(St-MMA-AA) copolymer photonic crystal arrays exhibited brilliant structural colours after a self-assembly process [ 18 , 26 , 27 , 28 , 29 ], which was generally synthesised by emulsion polymerisation that was based on the kinetic principles of free radical-initiated vinyl addition polymerisation [ 30 ]. There have been a few attempts at the study of achieving the stimuli-responsive behaviour of the photonic crystal films for amplifying their potential applications as sensing materials [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coals contain both nanoscale aromatic carbon (NSAC) and aliphatic amorphous carbon . So, coals can be the ideal source of carbon for preparing carbon quantum dots if these domains exfoliate in an efficient way to form a carbon quantum dot …”
Section: Introductionmentioning
confidence: 99%
“…Synthetic ways including “bottom‐up” or “top‐down” approaches have been used to prepare FCDs from small organic molecules and other carbon‐containing precursors. The “top down” approach is effective for low cost carbon sources such as graphite, fullerene, graphene oxide, carbon nanotubes, and carbohydrates . This method uses H 2 SO 4 , HNO 3 , KMnO 4 , and other strong acids and oxidantsto exfoliate FCDs, and suits large‐scale solution‐processing from easily‐acquired cheap carbon sources .…”
Section: Introductionmentioning
confidence: 99%